The impact of a 6-year comprehensive community trial on the awareness, treatment and control rates of hypertension in Iran: experiences from the Isfahan healthy heart program - Khosravi, Alireza (BioMed Central, 2010)
OBJECTIVES: We aimed to evaluate the changes over time in the prevalence, awareness, treatment, and control rate of hypertension in intervention and reference areas of a comprehensive community trial with reference area. METHODS: Data from independent sample surveys before and after implementation of the program (2001 vs.2007) were used to compare differences in the intervention and references areas over time. Hypertension was defined as blood pressure ≥140/90 mmHg in non-diabetic patients and ≥130/80 mmHg in diabetic individuals and or taking antihypertensive medications. Interventional activities included educational strategies at population level as well as for hypertensive patients, their families and health professionals. RESULTS: The study population of the baseline survey included 6175 (48.7% males) in the interventional area and 6339 (51.3% male) in the reference area. The corresponding figures in the post-intervention phase was 4717 (49.3% male) in the interventional area and 4853 (50.7% male) individuals in the reference area. The prevalence of hypertension had a non-significant decrease from 20.5%to 19.6%, in the interventional area whereas in the reference area, it increased from 17.4% to 19.6% (P = 0.003). If we consider Bp ≥ 140/90 in diabetic and non-diabetic patients as hypertension definition, the prevalence of hypertension in the interventional areas had a non-significant decrease from 18.9% in 2001 to 17.8% in 2007, whereas in the reference area, it had a significant rise from 15.7% to 17.9% (P = 0.002) respectively. Awareness, treatment and control rates of hypertension had better improvement in urban and rural part of the interventional area compared to reference area. The awareness, treatment, and control rates of hypertension increased significantly in the age groups of more than 40 years, as well as in all groups of body mass index in interventional areas without significant change in the reference area. Mean systolic blood pressure of study population in the interventional area decreased from 116.13 ±19.37 to 112.92 ± 18.27 mmHg (P < 0.001) without significant change in reference area. CONCLUSIONS: This comprehensive and integrated program of interventions was effective in tackling with the prevalence of hypertension, and may improve the awareness, treatment and control rates of this disorder in a developing country setting.